BENEFITS OF HEALTH AND SOCIAL CARE INTEGRATION. Issue 1 (1st March 2014) - Layden, J; Nicol, B; Connelly, M; Hekerem, Diana; Meade, R
Abstract : Introduction: Scotland's health boards and local authorities are moving towards integrated funding and service provision. Effective integration will depend on health, social care and third/independent sector partners pooling resources and planning care together, led by clinicians and other professionals. Working with a voluntary sector expert as a partner in service design can enable these principles to be put into practice in palliative care. Aim(s) and method(s): Marie Curie Service Development in Scotland's principles are whole system review and development of services; identifying opportunities for collaborative working; and implementing cross sector initiatives and partnerships. Demographic and activity data, stakeholder focus groups and workshops, service user survey and NHS and Scottish Government programme assurance have been used to design, review and improve integrated services and programmes. Results: Integrated Health and Personal Care Community Support – Over 77 patients would have required hospital admission without the integrated service. 83% of respondents thought the service had enabled more input into decision making about their care; and 66% were able to spend more time with their loved ones, and have reported an improved quality of life. Redesign Programmes – The 3 redesign programmes collaboratively bring together health, social care and third/independent sector partners at both strategic and operational levels. Conclusion(s): The voluntary sector as a key partner in supporting the integration agenda with specific expert knowledge. For palliative care, Marie Curie can test new ways of working and develop community focused collaborations, with evidence of benefits to patients and families as well as the health economy.